Proceedings of the Conference on Human Language Technology and Empirical Methods in Natural Language Processing - HLT '05 2005
DOI: 10.3115/1220575.1220618
|View full text |Cite
|
Sign up to set email alerts
|

Extracting product features and opinions from reviews

Abstract: Consumers are often forced to wade through many on-line reviews in order to make an informed product choice. This paper introduces OPINE, an unsupervised informationextraction system which mines reviews in order to build a model of important product features, their evaluation by reviewers, and their relative quality across products. Compared to previous work, OPINE achieves 22% higher precision (with only 3% lower recall) on the feature extraction task. OPINE's novel use of relaxation labeling for finding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
699
0
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,145 publications
(731 citation statements)
references
References 26 publications
(24 reference statements)
1
699
0
10
Order By: Relevance
“…This includes identifying expressions or sentences that are subjective in the context of a particular text or conversation (e.g., Yu and Hatzivassiloglou, 2003;Nasukawa and Yi, 2003;Popescu and Etzioni, 2005)), identifying particular types of attitudes (e.g., (Gordon et al, 2003;Liu, Lieberman, and Selker, 2003)), recognizing the polarity or sentiment of phrases or sentences (e.g., (Morinaga et al, 2002;Yu and Hatzivassiloglou, 2003;Nasukawa and Yi, 2003;Yi et al, 2003;Kim and Hovy, 2004;Hu and Liu, 2004;Popescu and Etzioni, 2005;Wilson, Wiebe, and Hoffman, 2005)), identifying who is expressing an opinion (Kim and Hovy, 2004;Choi et al, 2005), and identifying levels of attributions (e.g., that it is according to China that the U.S. believes something) (Breck and Cardie, 2004).…”
Section: Research In Subjectivity and Sentiment Analysismentioning
confidence: 99%
“…This includes identifying expressions or sentences that are subjective in the context of a particular text or conversation (e.g., Yu and Hatzivassiloglou, 2003;Nasukawa and Yi, 2003;Popescu and Etzioni, 2005)), identifying particular types of attitudes (e.g., (Gordon et al, 2003;Liu, Lieberman, and Selker, 2003)), recognizing the polarity or sentiment of phrases or sentences (e.g., (Morinaga et al, 2002;Yu and Hatzivassiloglou, 2003;Nasukawa and Yi, 2003;Yi et al, 2003;Kim and Hovy, 2004;Hu and Liu, 2004;Popescu and Etzioni, 2005;Wilson, Wiebe, and Hoffman, 2005)), identifying who is expressing an opinion (Kim and Hovy, 2004;Choi et al, 2005), and identifying levels of attributions (e.g., that it is according to China that the U.S. believes something) (Breck and Cardie, 2004).…”
Section: Research In Subjectivity and Sentiment Analysismentioning
confidence: 99%
“…Previous work on unsupervised sentiment classification has shown that adjectives and adverbs are good indicators of sentiment (Hatzivassiloglou, 1997(Hatzivassiloglou, , 2000, [19], Turney 2002 [5]). It has also been shown that adjectives present around a given topic are indicative of sentiment related to the particular topic [11], [20]. Hence we first use a Part of Speech (POS) tagger to identify adjectives present in the snippet.…”
Section: ) Default Classifiermentioning
confidence: 99%
“…The precision of step 1 of the above algorithm was improved by Popescu and Etzioni in [77]. Their algorithm tries to remove those noun phrases that may not be product features.…”
Section: Feature Extraction From Reviews Of Formatmentioning
confidence: 99%
“…Here, we only describe a lexicon-based approach to solving the problem [19,36]. See a more complex method based on relaxation labeling in [77].…”
Section: Opinion Orientation Identificationmentioning
confidence: 99%